(3LhGgQ GdCSQGQ aj eYGQa GdCMLGQs - (3Ydj LdHj Hf NSQh GdGRfjbj, GdeDda GdLOjO hGdTjN GdQhHj,J (B1018 (3g` s
(3ChdgG (B:s
(3hHYO aEfi CNQLJ ef HMQ GdYhGQa dWGFa hOQQ GdeYGQa s
(3BNQgG (B:s
(3Ef GdaVg EPG JcdS HebOGQ Kefg ef GdbdYi GdeOHQ NeS eQGJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B327 - (3U(B339s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B53s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B667 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B34 s
Keywords: (3GdcjejGA h GdWHjYjGJs